Machine learning methods for the analysis of MEG data - Roberts, EJ (2024)
Neuroimaging data is often high-dimensional and difficult to interpret. Methods have been developed which can be applied to datasets to make them more malleable and comprehensible to researchers. This process is critical for improving our understanding of the nature of the brain. The developments made through neuroscientific research have the potential to transform the lives of many people, and making progress in the development of new methods is an important part of the discovery pipeline.